2009
DOI: 10.1038/leu.2009.93
|View full text |Cite
|
Sign up to set email alerts
|

Flow cytometric immunobead assay for the detection of BCR–ABL fusion proteins in leukemia patients

Abstract: BCR-ABL fusion proteins show increased signaling through their ABL tyrosine kinase domain, which can be blocked by specific inhibitors, thereby providing effective treatment. This makes detection of BCR-ABL aberrations of utmost importance for diagnosis, classification and treatment of leukemia patients. BCR-ABL aberrations are currently detected by karyotyping, fluorescence in situ hybridization (FISH) or PCR techniques, which are time consuming and require specialized facilities. We developed a simple flow c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

4
53
0
1

Year Published

2009
2009
2019
2019

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 67 publications
(58 citation statements)
references
References 38 publications
4
53
0
1
Order By: Relevance
“…However, when we used lysates from mature myeloid cells, the fluorescent signals in the BCR-ABL immunobead assay were clearly weaker than expected [29]. Additional experiments showed that the lower signals were caused by protein degradation via protease activity from the granules in more mature myeloid cells, such as granulocytes as well as CML cells.…”
Section: Immunobead Assay For the Detection Of Bcr-abl Fusion Proteinsmentioning
confidence: 77%
See 3 more Smart Citations
“…However, when we used lysates from mature myeloid cells, the fluorescent signals in the BCR-ABL immunobead assay were clearly weaker than expected [29]. Additional experiments showed that the lower signals were caused by protein degradation via protease activity from the granules in more mature myeloid cells, such as granulocytes as well as CML cells.…”
Section: Immunobead Assay For the Detection Of Bcr-abl Fusion Proteinsmentioning
confidence: 77%
“…in the ABL-SH2 domain. By using these two antibodies against "outer" epitopes, the BCR-ABL immunobead assay was expected to recognize all types of BCR-ABL fusion proteins, independent of the breakpoint position [29,30].…”
Section: Immunobead Assay For the Detection Of Bcr-abl Fusion Proteinsmentioning
confidence: 99%
See 2 more Smart Citations
“…Determination of BCR/ABL fusion gene is important for early diagnosis, prognosis, and even better for CML patients during the treatment [18]. Nowadays, several methods have been applied to recognize BCR/ABL fusion gene, such as flow cytometry (FCM) [19], fluorescence in situ hybridization (FISH) [20] and real-time Contents lists available at ScienceDirect journal homepage: www.elsevier.com/locate/optcom quantitative reverse transcription polymerase chain reaction (RT-PCR) [18]. These attractive methods are able to efficiently and accurately detect BCR/ABL fusion gene.…”
Section: Introductionmentioning
confidence: 99%